Recommendation of Customized Learning Strategies Based on the CHAEA Test - Ospina Herran, Alejandra; Rodríguez Marín, Paula Andrea; Duque Méndez, Nestor Darío (Scientia et Technica, 2018)
Generally, the educational strategies that apply to a group of students are the same, without addressing the fact that all students learn and process information differently. As an alternative to this situation, this article presents a proposal aimed at defining various activities that support pedagogical strategies and attend to the specific characteristics of students, especially learning style. A content-based recommendation system was implemented that, based on the student's learning style obtained through CHAEA, determines and recommends activities according to the strategies that best fit the student's profile. The proposal was validated in two (2) university institutions in Colombia and in dissimilar subjects; The results are promising and can be applied in different courses and in virtual, blended and classroom environments.